The role of intravoxel incoherent motion diffusion-weighted magnetic resonance imaging in the diagnosis and staging of diabetes nephropathy - Li Yue-ming; Hu Run-yue; Wei Xiao-bao; Ni Li-hua; Jie Hao; Xu Hai-bo; Wu Xiao-yan (Linchuang shenzangbing zazhi, 2025)
ObjectiveTo evaluate changes in the perfusion fraction and diffusion coefficient via the intravoxel incoherent motion diffusion-weighted magnetic resonance imaging（IVIM-DWI）， and to assess changes in the renal function and damage in different urinary protein periods of diabetes kidney disease （DKD）.MethodsFrom June 16， 2020 to October 31， 2023， 50 patients with type 2 diabetes mellitus （DM） in Zhongnan Hospital of Wuhan University were included in the present study. According to the presence or absence of microalbuminuria and the value of albumin/creatinine ratio （ACR），patients were divided into the DM group （n=19， ACR<300 mg/g）， early DKD group （EDKD ， n=16， 30 mg/g≤ACR≤300 mg/g）， and advanced DN group （ADKD， n=15， ACR>300 mg/g）， and 21 healthy people were recruited as the control group. IVIM-DWI parameters were obtained and compared， including the perfusion fraction（f）， true diffusion coefficient （D）， and pseudo diffusion coefficient （D*）.Correlation analysis between the above indices and clinical indicators like ACR and estimated glomerular filtration rate （eGFR） was performed. Receiver operating characteristic （ROC） curves were plotted to analyze the diagnostic efficacy of relevant parameters in distinguishing DM from EDKD and ADKD.ResultsThe f values of the cortex and medulla in the DM group significantly increased compared to the control group， which were significantly lower in the EDKD group than the DM group， but comparable to the control group. The f values of the cortex and medulla in the ADKD group were significantly lower than the control group， DM group and EDKD group （F=267.72， and 134.41，respectively； both P<0.001）.Compared with the control group， the D values of the cortex were significantly lower in the DM， EDKD and ADKD groups （F=37.83， all P<0.001）. The D values of the medulla in the EDKD group were significantly higher than the control group and DM group （F=5.57， P=0.002）. The D* values of the cortex were significantly lower in the ADKD group than the DM group （F=4.13， P<0.01）. The D* values of the medulla in the EDKD and ADKD groups were significantly higher than those of the control group and DM group （F=6.37， P=0.004）. The medullary F-value in the ADKD group was positively correlated with ACR （r=0.63， P=0.011）， while the cortical D-value in the DM group， EDKD group， and ADKD group was negatively correlated with ACR （r=-0.878， -0.906， -0.978， all P<0.001）. The medullary D-value in the DM group was negatively correlated with ACR （r=-0.812， P<0.001）. The groups is cortical f-value had the best diagnostic performance in distinguishing DM from EDKD， with an area under the curve （AUC） of 0.977， a cutoff value of 0.350， a sensitivity of 0.895， and a specificity of 1.000. Cortical and medullary F-values had the best diagnostic efficacy indistinguishing EDKD from ADKD， with an AUC of 1.000， cutoff values of 0.219 and 0.153， and sensitivity of 1.000，ConclusionIVIM-DWI can reflect the changes in renal perfusion and water molecule diffusion function in DKD， which can be used to evaluate the renal function damage of diabetes nephropathy and assist in clinical staging.